An Analysis on the Feasibility of Financial Valuation of Technology Companies Based on Value Investing - Chen, Zhonghui (Transactions on Economics, Business and Management Research, 2024)
This research explores the critical issue of accurately valuing internet companies in today’s business environment, highlighting the inadequacies of traditional valuation methods like Net Present Value (NPV) and Price to Earnings (PE) ratios for this sector. By conducting a fundamental analysis rooted in value investing principles, this study examines 2022 financial data from thirteen internet companies listed among Forbes Global Technology firms. It scrutinizes key financial metrics such as liquidity, debt-servicing capability, profitability, and shareholder returns. The analysis reveals that these companies experience cash flow challenges affecting their liquidity. Despite having a moderate long-term debt ratio, they heavily depend on debt financing and struggle with interest payments. While capable of generating profits, these firms face stiff competition and significant cost pressures. Market sentiment remains highly optimistic about the future of internet companies, resulting in high valuations. Given the favorable market conditions, it is crucial for internet companies to strategically enhance their competitive edge, improve core product competitiveness, and increase profitability through innovative operational and marketing strategies, thereby boosting their industry presence and societal impact.